Experimental and simulation study of CO2 and H2S solubility in propylene carbonate, imidazolium-based ionic liquids and their mixtures. (January 2020) - Zhao, Zhijun; Huang, Ying; Zhang, Zhaohuan; Fei, Weiyang; Luo, Mingsheng; Zhao, Yongsheng
Highlights: The CO2 and H2 S solubility and the selectivity of H2 S/CO2 in PC, [Omim][BF4 ], and their mixtures were investigated. Adding [Omim][BF4 ] into PC can increase the CO2 and H2 S solubility compared with the pure PC. Adding [Omim][BF4 ] into PC can decrease the vapor pressure of PC in their mixtures. The COSMO-RS-Lei model is in much better agreement than COSMO-RS (ADF) for predicting both CO2 and H2 S solubility. Abstract: Currently, solvent-based absorption is known as an effective technology to capture acid gases, e.g., CO2 or H2 S. In this work, the constant-volume method is used to determine CO2 and H2 S solubility in propylene carbonate (PC), imidazolium-based ionic liquids (ILs): 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4 ], 1-hexyl-3-methylimidazolium tetrafluoroborate [Hmim][BF4 ], and 1-octyl-3-methylimidazolium tetrafluoroborate [Omim][BF4 ], and their mixtures at temperature from 303.15 to 333.15 K under pressures up to about 1 MPa. Besides, the quantum chemistry-based COSMO-RS models are used to predict the vapor pressure and the solubility in these solvents. The experimental results illustrate that adding [Omim][BF4 ] into PC can improve the CO2 and H2 S solubility and the H2 S/CO2 selectivity compared with the pure PC, which increases with the increasing [Omim][BF4 ] mass fraction in the mixtures. The simulation with COSMO-RS shows the vapor pressures of PC in the mixtures decreases with the increasing [Omim][BF4 ] mass fraction. Moreover, the prediction results show that COSMO-RS-Lei model is in much better agreement than COSMO-RS (ADF 2005) for predicting both CO2 and H2 S solubility and the prediction accuracy of CO2 is better than that of H2 S. Finally, the mixtures of PC and [Omim][BF4 ] may be used as promising physical solvents to capture CO2 and H2 S selectively with high partial pressures because they connect the advantages of organic solvents and ILs.